Attachment, Trauma, and Mentalization in Intimate Partner Violence: A Preliminary Investigation. Issue 11 (June 2022) - Condino, Valeria; Giovanardi, Guido; Vagni, Monia; Lingiardi, Vittorio; Pajardi, Daniela; Colli, Antonello
Intimate partner violence (IPV) has been examined from a range of theoretical perspectives, including attachment theory, with the aim of assessing psychosocial risk factors. Previous research has shown that a child's exposure to violence in the family is a major predictor of IPV victimization later in life. Furthermore, research on abused and traumatized adult samples has shown high frequencies of unresolved/disorganized attachment styles. In particular, disorganized attachment is associated with major problems of affect regulation and deficits in mentalizing ability. The present research had three aims: (a) to assess the childhood traumatic experiences of female victims of IPV; (b) to investigate and identify the attachment patterns of female victims of IPV; and (c) to examine reflective functioning and prementalistic modes in female victims of IPV, in relation to attachment and trauma. A sample of 31 women, recruited through anti-violence centers, were administered the Adult Attachment Interview (AAI) and the Reflective Functioning Questionnaire. The Complex Trauma Questionnaire and the Reflective Functioning Scale (RFS) were also applied to the AAI transcripts. Interviews were audio recorded and transcribed verbatim. Coding was conducted by two trained coders and certified as reliable for the AAI and RFS. Clinicians completed the Modes of Mentalization Scale (MMS) to assess participants' mentalization style. The data showed a high percentage of women with insecure attachment and lower reflective functioning. The results are discussed in terms of their clinical and theoretical implications—particularly their application to psycho-forensics, through the development of preventive programs and interventions for IPV. Efforts to understand the etiology of IPV and to intervene to prevent recidivism are fundamental in reducing this public health threat.